Effect of thermal modification of wood on adhesion and strength properties of wood-cement composition - V. Yu. Chernov; E. S. Sharapov; E. M. Mal’ceva; E. N. Pegushina (Vestnik MGSU)
Introduction. The adhesion properties and factors influencing the formation of the composition of thermally modified timber (TMT) and cement are investigated. The results were focused on the creation of a new material with improved service properties, which is named thermo-wood concrete (TWC).Materials and methods. Adapted standard methods to assess the adhesion of sand-cement mortar with TMT and compressive strength of sand-cement mortar obtained on waters infused with different types of wood and TMT were applied. The influence of the following factors was considered: the intensity (classes) of wood thermal modification, wood species, mortar formation method, cement binder content, wood surface conditions and moisture content of TMT, the presence of final steam curing of specimens.Results. The sand-cement mortar with a high content of cement binder had the highest adhesion with TMT. PVA-emulsion solution resulted in additional slight improvement of the sand-cement mortar and TMT adhesion. In general, unmodified (natural) wood had higher adhesion in comparison with TMT under the same conditions. Negative factors included premoistening of thermally modified timber surface, cleaning and leveling of its surface and the use of coniferous species for TMT specimens. The strength of sand-cement mortar was the lowest for specimens with addition of PVA-emulsion. Factor of water purification after infusion with TMT and unmodified wood had insignificant effect on strength of sand-cement mortar.Conclusions. TMT-cement composition had a lower adhesive force in comparison with unmodified wood. This is due to the combined effect of low hygroscopicity and wettability of the TMT surface. Water washing of the TMT is inappropriate due to deterioration of adhesion properties of the filler in TWC. To increase the adhesion of the components, it is recommended to use mortars with a high content of cement binder.